1996
DOI: 10.1002/(sici)1097-0142(19960801)78:3<396::aid-cncr3>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Gastric lesions in 76 patients with adult T-cell leukemia/lymphoma: Endoscopic evaluation

Abstract: This study demonstrated that 30.3% of patients with ATLL had gastric involvement and 13.2% had peptic ulcers. Gastric involvement of ATLL was one of the prognostic factors in acute type ATLL, whereas it had no influence on the prognosis of lymphoma type ATLL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 19 publications
5
18
0
Order By: Relevance
“…Adult T-cell leukemia/lymphoma (ATLL) is a devastating T-cell malignancy caused by HTLV-1 [7,8]. ATLL is characterized by a high tendency for leukemic cells to infiltrate various organs including the stomach [9]. Sakata et al demonstrated gastric infiltration of ATLL cells in 23 of 76 patients with ATLL (30.3%) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult T-cell leukemia/lymphoma (ATLL) is a devastating T-cell malignancy caused by HTLV-1 [7,8]. ATLL is characterized by a high tendency for leukemic cells to infiltrate various organs including the stomach [9]. Sakata et al demonstrated gastric infiltration of ATLL cells in 23 of 76 patients with ATLL (30.3%) [9].…”
Section: Introductionmentioning
confidence: 99%
“…ATLL is characterized by a high tendency for leukemic cells to infiltrate various organs including the stomach [9]. Sakata et al demonstrated gastric infiltration of ATLL cells in 23 of 76 patients with ATLL (30.3%) [9]. In contrast, the other gastric T-cell lymphomas without HTLV-1 infection are reported sporadically [6].…”
Section: Introductionmentioning
confidence: 99%
“…The patients included 47 men and 24 women with a mean age of 59 years (range, 33–82 years). ATLL was diagnosed based on the following criteria5, 6, 16: 1) seropositivity against HTLV‐1 tested using a particle agglutination kit (Serodia HTLV‐1; Fuji‐Rebio Company, Tokyo, Japan) and, when indicated, confirmed by an enzyme immunoassay kit (Eitest‐ATL; Eisai Company, Tokyo, Japan); 2) lymphoid neoplasia confirmed histologically and/or hematologically (abnormal lymphoid cells with nuclear irregularity of lobulation and clover‐leaf forms); 3) CD3+, CD4+, CD8−, CD25+, and CD45RO+ immunophenotypes of tumor cells analyzed using a FACSscan flow cytometer (Becton Dickinson, Mountain View, CA); and 4) monoclonal integration of HTLV‐1 provirus in chromosomal DNA by Southern blot analysis 17. The clinical type of ATLL was classified into four groups (acute, lymphoma, chronic, and smoldering) based on the report by the Lymphoma Study Group 16…”
Section: Methodsmentioning
confidence: 99%
“…ATLL is characterized by a high tendency of leukemic cells to infiltrate various organs 3, 4. Gastrointestinal involvement in patients with ATLL also is common 5, 6. Recently, Sakata et al6 demonstrated gastric infiltration of ATLL cells in 23 of 76 patients with ATLL (30.3%).…”
mentioning
confidence: 99%
See 1 more Smart Citation